The Morphology and Bending Behavior of Regenerated Costal Cartilage with Kawanabe-Nagata Method in Rabbits – the Short Term Result of an Experimental Study. Issue 10 (17th September 2021) - Han, Jingjian; Cuomo, Roberto; Zhao, Yanyong; Pan, Bo; Yang, Qinghua
Abstract: Background: The chest wall deformity is a well-known complication following costal cartilage harvest with the biomechanical factor considered to be a cause of this donor-site morbidity. Kawanabe-Nagata method is a widely-accepted approach to prevent the deformity. However, knowledge about the biomechanical properties of regenerated costal cartilage is limited, and the value of reimplantation of autologous costal cartilage blocks is not clear. Methods: The fifth costal cartilage on both sides of six male, 8 weeks of age, New Zealand white rabbits were harvested with the perichondrium preserved intact in situ. The perichondrium was sutured to form a perichondrial pocket and part of the excised costal cartilage was cut into 0.5 mm cartilage blocks and returned to the perichondrial pocket of left side. The animals were sacrificed 16 weeks postoperatively and the regenerated and a piece native costal cartilage was harvested for morphological and three point bending test. Results: There was no remarkable chest wall deformity in all animals, and there were no apparent differences in the appearance of the regenerated cartilage with and without reimplantation autologous cartilage blocks. The elastic modulus of native cartilage was significantly higher than the regenerated cartilage. The stiffness of regenerated cartilage without reimplantation was higher than that of with reimplantation, but this difference was not significant. Conclusions: The stiffness of regenerated cartilage was significantly lower than the native cartilage. Reimplantation of autologous cartilage blocks was not superior to that without reimplantation in regard to restoring the volume defect and strengthening the regenerated cartilage.